2022
DOI: 10.1002/acr.25001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Knee Biomechanics and Pain in People With Knee Osteoarthritis: A Systematic Review and Meta‐Analysis

Abstract: Objective Our primary aim was to determine the cross‐sectional relationship between knee biomechanics during gait and pain in people with medial knee osteoarthritis. Our secondary aim was to evaluate differences in knee biomechanics between symptomatic and asymptomatic participants with medial knee osteoarthritis. Methods Four online databases were searched from inception to July 2021. Eligible studies included people with medial/nonspecific knee osteoarthritis and a reported relationship between knee biomecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 90 publications
1
12
0
Order By: Relevance
“…Primary osteoarthritis (OA) [ 17 ] is defined as a chronic disabling disease with a familial genetic predisposition [ 18 ], whereas secondary OA is frequently initiated by excessive joint loads or overuse that cause wear and tears at the surface of the articular joint cartilage [ 19 ]. Primary OA is mostly related to overweight, aging, and heredity.…”
Section: Definition and Treatment Of Osteoarthritis (Oa)mentioning
confidence: 99%
“…Primary osteoarthritis (OA) [ 17 ] is defined as a chronic disabling disease with a familial genetic predisposition [ 18 ], whereas secondary OA is frequently initiated by excessive joint loads or overuse that cause wear and tears at the surface of the articular joint cartilage [ 19 ]. Primary OA is mostly related to overweight, aging, and heredity.…”
Section: Definition and Treatment Of Osteoarthritis (Oa)mentioning
confidence: 99%
“…11 It may also limit their overall selfcare ability and motivation, their endurance capacity, their ability to live independently, plus the pursuit of a desirable life quality. [10][11][12] In particular, the older adult suffering from disabling osteoarthritis may be more severely compromised than ever, 8 especially among those cases where COVID-19 post infection symptoms of fatigue, weakness, and dizziness prevail unabated 11 if the oxidative processes associated with COVID-19 further induce abnormal cell-matrix interactions within the osteoarthritic cartilage tissue, 13 as well as exacerbating prevailing levels of inflammation, pain, low selfefficacy perceptions, 14 and matrix damage attributable to the release of destructive enzymes. 15 This is supported by numerous loading studies ranging from those examining the impacts of joint immobilization to those examining the outcomes of excessive joint loading 16 and others that imply that both too little movement as well as excessive repetitive movements can foster cartilage damage or render the bone beneath this tissue noncompliant 17 with dire functional and pain consequences, even if the individual is initially in good health, and especially if the older adult already suffers from osteoarthritis of one or more joints, 18 and is a woman.…”
Section: Osteoarthritismentioning
confidence: 99%
“…However, when pain scores and facial activity do not fully explain the variation in movement asymmetry in the statistical models, the question is whether this assumption is valid. In human research, the difficulties reported in correlating biomechanical parameters to self-reports of pain illustrate that movement asymmetry may not represent the full pain experience (as reviewed by Hutchison et al, 2022). Instead, facial expressions of pain in humans are sensitive and specific (Kunz et al, 2004;Prkachin & Solomon, 2009).…”
Section: Using Movement Asymmetry As a Proxy For Painmentioning
confidence: 99%